PERANAN TEKNOLOGI INFORMASI DALAM AUDIT - Ika Rochmawati Oktavia (Jurnal Ekonomi Akuntansi dan Manajemen, 2015)
Information technology has changed the business transaction, recording dan business process. When most financial information exist in electronic form, auditors should consider audit procedures. In the other hand, the use of information technology can be used to improve the audit techniques and tools. The information technology also can help auditor increase their productivity, as well as that of the audit function. Generalized audit software is the tool use by auditors to automate various audit tasks. This method is rarely used by auditors because they have to examine the whole data. It will takes more time and more money. When accounting and electronic data interchange popularizing, the computerized audit tools are becoming more necessary. With electronic data interchange, an entity and it’s customers or suppliers use communication links to transact business electronically, but some electronic evidence may exist for only a short time and be irretrievable after a specified period if files are changed and backup files do not exist. Thus, auditors should consider the time during which information exists or is available in determining the nature, timing and extent of their substantive tests and applicable tests of controls.